2013
DOI: 10.1159/000355476
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of Breast Ductal Carcinoma in situ with ALDH1-Positive Cancer Stem Cells

Abstract: Objective: The aim of this study was to elucidate the clinicopathological characteristics of breast ductal carcinomas in situ (DCIS) with aldehyde dehydrogenase 1 (ALDH1)-positive cancer stem cells (CSCs). Methods: DCIS (n = 194) were subjected to immunohistochemical staining and results were examined for associations with various clinicopathological parameters. The ALDEFLUOR assay for breast cancer cell lines was also performed to determine the proportion of CSCs according to intrinsic subtype. Results: DCIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Second, cancer stem cell model. As TN breast cancer cells have more percentage of cancer stem cells than the other subtypes, we have good excuses to expect and assume that PAM is more effective in killing cancer stem cells. This feature, once true, makes PAM a promising oncotherapeutic approach as it may eradicate cancer stem cells that is the source of metastasis and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Second, cancer stem cell model. As TN breast cancer cells have more percentage of cancer stem cells than the other subtypes, we have good excuses to expect and assume that PAM is more effective in killing cancer stem cells. This feature, once true, makes PAM a promising oncotherapeutic approach as it may eradicate cancer stem cells that is the source of metastasis and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Independence from exogenous estrogen is unsurprising given the ER-negativity of SUM-225 cells, but an asset in the sense that slow-growing murine tumors of this nature may better represent indolent DCIS tumors than models requiring supplementation with supraphysiological estrogen levels. Furthermore, since coincident ER-negativity/HER2-positivity in DCIS patients has been associated with larger tumors and increased recurrence rates [ 33 ], in addition to cancer stem cell enrichment [ 34 ], the subset of DCIS patients represented by SUM-225 cells has greater need of new drug targets than the majority of DCIS patients with low-risk ER-positive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Based on immunohistochemistry analysis of CD24 and CD44 expression in 50 breast cancer patients, Idowu MO also suggested that CD24-CD44+ BCSCs played a significant role in triple negative subtype of breast cancer [ 39 ]. In addition, Tsukabe M found that ALDH+ BCSCs were more likely to overlap with HER2-positive tumor cells while luminal A subtype displayed low ALDH1 activities [ 36 ]. Similar with Tsukabe M, Park SY discovered that the frequency of ALDH1-positive cells was higher in HER2+ breast tumors than luminal breast tumors [ 37 ].…”
Section: Effect Of Bcscs On the Metastatic Organotropism In Breast Cancermentioning
confidence: 99%